Managing salinity in north-west India: the conjunctive use option - Tyagi, N. K., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
North-West India which comprises south-western Punjab, northern Haryana and north-western Rajasthan is a region with distinct agro-ecology with peculiar land and water management problems. The major part of the area lies in a semi-arid to hyper-arid zone where evaporation exceeds rainfall by a factor of 2 to 15. Alluvial deposits that underlie most of the area, contain to a great depth, a continuous body of water which occurs under phreatic conditions in a large part of the area with few semi-confined to confined aquifers occurring at varying depths. The ground water availability as well as quality decreases with increase in aridity from northeast to southwest. To correct the water demand/supply imbalance in this agriculturally productive region, extensive irrigation has been introduced through large scale diversion of surface water. In spite of surface water diversions, the water availability per unit area is low and the region is under the influence of waterlogging, salinity and alkalinity which are undermining the capacity of the region to meet its food production targets. Various long and short term options including preventive and curative measures have been examined to maintain the agricultural productivity at high levels. The long term solution lies in provision of drainage to lower the water table and leach salts, which should be disposed in a permanent sink. The existing geopolitical situation and the absence of natural drainage outlets favour conjunctive use of marginal quality ground waters and drainage effluents with canal waters to tide over the water scarcity, to minimize the rise of the watertable and to reduce the disposable drainage effluents. In land areas afflicted with salinity under high watertable situations, conjunctive use is permissible only in conjunction with sub-surface drainage. Agrochemical amendments together with salt tolerant cultivars promote the use of high residual sodium carbonate waters in a medium term plan. In areas with deep watertable but with high ground water salinity, cropping choices are limited and salt tolerant trees/halophytes are better options. Conjunctive use planning in ground water areas with a declining trend calls for increased emphasis on ground water recharge to sustain the existing cropping pattern. In the absence of large scale investment in the near future, the technical and socio-economic situation favours conjunctive use as medium term option for managing salinity in North-West India.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.